2022
DOI: 10.18632/aging.203843
|View full text |Cite
|
Sign up to set email alerts
|

Five years of exercise intervention at different intensities and development of white matter hyperintensities in community dwelling older adults, a Generation 100 sub-study

Abstract: We investigated if a five-year supervised exercise intervention with moderate-intensity continuous training (MICT) or high-intensity interval training (HIIT) versus control; physical activity according to national guidelines, attenuated the growth of white matter hyperintensities (WMH). We hypothesized that supervised exercise, in particular HIIT, reduced WMH growth. Older adults from the general population participating in the RCT Generation 100 Study were scanned at 3T MRI at baseline (age 70-77), and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 91 publications
(119 reference statements)
1
5
0
Order By: Relevance
“…Moreover, higher exercise intensity, irrespective of group, was associated with lower Cho/ Cr in the same part of the hippocampus. The MRSI results are in line with structural MRI results from the same cohort showing that the SEG group had higher rates of hippocampal atrophy [20] and white matter hyperintensity growth [105] than the CG. Additionally, our results demonstrate that sLASER allows for a detailed investigation of spatially specific metabolic profiles along the hippocampal long axis, and that the neurochemical profiles were more closely associated with functional outcome than for instance the hippocampal volume.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, higher exercise intensity, irrespective of group, was associated with lower Cho/ Cr in the same part of the hippocampus. The MRSI results are in line with structural MRI results from the same cohort showing that the SEG group had higher rates of hippocampal atrophy [20] and white matter hyperintensity growth [105] than the CG. Additionally, our results demonstrate that sLASER allows for a detailed investigation of spatially specific metabolic profiles along the hippocampal long axis, and that the neurochemical profiles were more closely associated with functional outcome than for instance the hippocampal volume.…”
Section: Discussionsupporting
confidence: 84%
“…15 The authors of both studies postulated that more vigorous and frequent exercise may be required for WMH volume attenuation over time. 14,15 Sex differences in AT efficacy may be another reason why these RCTs did not find intervention effects. 14,15 In a secondary analysis of the PROMoTE study (Promotion of the Mind Through Exercise)-which assessed the effect of a 6-month moderate-intensity AT walking program compared with a control group in people with CSVD and mild cognitive impairment-no significant group differences in WMH progression were observed.…”
Section: Effect Of Pa and Exercise On Csvd-related Brain Damage Csvd ...mentioning
confidence: 97%
“…15 The authors of both studies postulated that more vigorous and frequent exercise may be required for WMH volume attenuation over time. 14,15…”
Section: Effect Of Pa and Exercise On Csvd-related Brain Damagementioning
confidence: 99%
See 1 more Smart Citation
“…131 The authors acknowledged that the sample size of this meta-analysis remained insufficient to detect a significant benefit of incident dementia. Small RCTs showed that exercise did not attenuate WMH progression nor improve white matter integrity in older adults, [132][133][134] while another small RCT suggested that dancing (ie, combining physical, cognitive, and social engagement) may maintain white matter integrity. 135 Meta-analysis including both observational studies and RCTs showed that intentional weight loss among obese/overweight people was associated with improvement in cognitive functions.…”
Section: Other Lifestyle-related Vascular Risk Factors and Behavioral...mentioning
confidence: 99%